Isobolographic analysis of the hypnotic interaction between propofol and thiopental - Wong, Wai Hong; Lim, Thiam Aun; Lim, K. Y. (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2010)
Introduction: Giving two intravenous anaesthetic agents simultaneously generally results in an additive effect. The aim of this study was to investigate the interaction between propofol and thiopental when given to patients who have had sedative premedication. Methods: Fifty patients were admitted into the study. All patients received oral midazolam 3.75 mg and intravenous fentanyl 100 mg before induction of anaesthesia. Twenty patients received an infusion of either propofol or thiopental while 30 patients received an infusion of an admixture of both drugs. Isobolographic analysis was used to determine the interaction between the two drugs. Results: The interaction between propofol and thiopental was additive. The average dose at loss of the eyelash reflex for propofol and thiopental was 0.71 mg kg-1 and 1.54 mg kg-1 respectively. Premedication decreased the induction dose by 38.2%. Conclusion: Propofol and thiopental interact in an additive fashion when given at induction of anaesthesia.